2001
DOI: 10.1074/jbc.m102061200
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Induces Rac1-dependent Reactive Oxygen Species Formation and Coordinates Tumor Necrosis Factor-α Secretion through IKK Regulation of NF-κB

Abstract: Reactive oxygen species (ROS) are important second messengers generated in response to many types of environmental stress. In this setting, changes in intracellular ROS can activate signal transduction pathways that influence how cells react to their environment. In sepsis, a dynamic proinflammatory cellular response to bacterial toxins (e.g. lipopolysaccharide or LPS) leads to widespread organ damage and death. The present study demonstrates for the first time that the activation of Rac1 (a GTP-binding protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
311
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 376 publications
(331 citation statements)
references
References 93 publications
16
311
0
2
Order By: Relevance
“…Moreover, we recently reported 25 that apoptosis induced by ischemia and reperfusion in the heart at least in part depends on Fas-L, TNF␣ and TRAIL, three NF B-regulated death ligands. [26][27][28] In the present study, TNF␣ mRNA, as well as apoptosis, was found to be reduced in NF B decoy ODN-treated hearts in comparison to control hearts, suggesting that NF B decoy ODN application does not result in an increased rate of apoptosis if TNF␣ expression is not up-regulated.…”
Section: Figure 4 Nf B Decoy Odn Retroinfusion + Ib4 Reduces Apoptosisupporting
confidence: 50%
“…Moreover, we recently reported 25 that apoptosis induced by ischemia and reperfusion in the heart at least in part depends on Fas-L, TNF␣ and TRAIL, three NF B-regulated death ligands. [26][27][28] In the present study, TNF␣ mRNA, as well as apoptosis, was found to be reduced in NF B decoy ODN-treated hearts in comparison to control hearts, suggesting that NF B decoy ODN application does not result in an increased rate of apoptosis if TNF␣ expression is not up-regulated.…”
Section: Figure 4 Nf B Decoy Odn Retroinfusion + Ib4 Reduces Apoptosisupporting
confidence: 50%
“…The following E1-deleted recombinant adenoviral vectors were used: (a) Ad.GPx-1, which encodes glutathione peroxidase 1 and degrades cytoplasmic H 2 O 2 (33); (b) Ad.Dyn(DN), which encodes a dominant-negative mutant (K44A) of dynamin and inhibits endocytosis (13); (c) Ad.NF-kBLuc, which encodes an NF-kB-responsive promoter driving luciferase expression and was used to assess NF-kB transcriptional activation in vivo (51); and (d) Ad.BglII, an empty vector with no insert, as a control for viral infection (33). For NF-kB transcriptional assays using infection with two recombinant adenoviruses, a slightly modified sequential infection method was used (51). In this case, cells were infected with experimental vectors [i.e., Ad.Dyn(DN) or Ad.GPx1] 24 h before infection with Ad.NFkBLuc], and cells were used for experiments at 48 h after initial infection.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, reactive oxygen species (ROS), such as O 2 -and H 2 O 2 , have been shown to be induced in cells after receptor stimulation with various ligands such as tumor necrosis factor alpha (TNF-a) (12,39), lipopolysaccharide (LPS) (24,51), angiotensin II (18), platelet-derived growth factor (PDGF) (56), insulin (37), epidermal growth factor (EGF) (2), and interleukin-1b (IL-1b) (6,39). Furthermore, the induction of ROS by these ligands has been suggested to be important for activating many of these signaling pathways (2,18,33,56).…”
Section: Introductionmentioning
confidence: 99%
“…NF-B activity was measured using a NF-B luciferase reporter adenovirus containing four tandem copies of the enhancer element located upstream of the firefly luciferase gene (36). This was provided by P. McCray, Jr. (University of Iowa, Iowa City, IA).…”
Section: Intracellular Ros and Nf-b Activitymentioning
confidence: 99%